Determination Of Workload And Number Of Optimal Workers For The Boiler Section Based On Pulse Rate And Working Sampling (Case Study : PT. Perkebunan Nusantara II PKS Pagar Merbau) - Dewi Paramita Sari (Journal Basic Science and Technology, 2021)
PT XYZ is the company used as the place of this research which is engaged in the production of Crude Palm Oil (CPO) and palm seeds (kernel). This company has a power plant station that uses a boiler that is useful for producing wet steam pressure which will be used for the production process of palm oil into CPO. The research was conducted on the boiler which has 4 workers. This research was conducted for 6 working days with a length of observation for 5 hours per day and the data taken was the pulse of workers before starting work and after finishing work as well as observation of work sampling with a total of 45 observations of data for each worker in one working day. The results of the calculation of cardiovascular load (%CVL) for all workers are in the interval 30% - < 60% with a physical workload category requires repair, and the productive percentage of all boiler workers is above 90%, and the one who has the largest productive percentage is worker 2, which is 97%. The optimal number of workers required by the boiler section at PT XYZ is 5 people so that the workload received by workers is reduced.